(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
The given article focuses on how pragmatics plays a crucial role in creating effective slogans. It highlights how context, implicature, and speech acts influence the interpretation and emotional impact of slogans. Using examples like Nike’s “Just Do It” and Apple’s “Think Different,” the article demonstrates how slogans evoke deeper meanings tied to cultural values and personal identity. The success of a slogan lies in its ability to create relevant, emotionally resonant messages that connect with the audience and encourage specific behaviors.